PENGARUH TERAPI KOMPRES HANGAT DENGAN AROMA LAVENDER TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST SECTIO CAESAREA DI RS. DETASEMEN KESEHATAN TENTARA (DKT) BENGKULU - Wahyu, Haifa; Febriawati, Henni; Lina, Liza Fitri; Andari, Fatsiwi Nunik; Wulandari, Restu (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Sectio saecarea (SC) is a method of giving birth to the fetus through an incision in the abdominal wall and uterine wall. One of the complications of SC is pain in the incision area. The non-pharmacological pain management strategy is to warm compress with the scent of lavender. The purpose of this study was to determine the effect of warm compress therapy with lavender aroma on decreasing pain intensity in post SC patients before and after warm compresses with aroma lavender. This type of research is quantitative research, with a pre-experimental research design method, using the design of one group pre test - post test design.        On the results of univariate analysis the pain intensity of post SC patients was obtained before a warm compress with lavender aroma in the hospital. The FKT Bengkulu in 2018 is 15 people (100%) Respondents experience moderate pain with a scale of 4-6. While the pain intensity of post SC patients after being warm compressed with lavender aroma is 12 people (80.0%) respondents experienced mild pain with a range of 1-3, and 3 people (20.0%) respondents with moderate pain intensity with a range of scales 4-6. The results of bivariate analysis showed that there was an effect of warm compress therapy with lavender aroma on the reduction in pain intensity in post SC patients in the hospital. Bengkulu DKT with a p-value of 0.01 0.05. It is recommended to RS.DKT Bengkulu to apply warm compress therapy with lavender aroma in the management of pain in post SC patients. Keywords: Sectio caesaria, pain, aroma of lavender